#FavelaLivesMatter: Youth from Urban Peripheries, Political Engagement and Alternatives to the War on Drugs. Issue 2 (4th June 2019) - ,
This article aims to share the experience of Movimentos (Movements), a collective of young activists from Brazilian favelas and peripheral neighborhoods whose goal is to discuss alternatives to the current drug policy from the peripheral youth's standpoint. The population's role in the formulation, application, and enforcement of public safety and drug policies is rudimentary, and the opportunities available to youngsters who live in Brazilian favelas and the outskirts are even smaller. The purpose of Movimentos is to have youngsters from the outskirts take center stage in the debate over public safety and drug policies, because they are the war on drugs greatest victims. The collective follows a hybrid organizational model that combines collective, horizontal governance with the institutional support of an academic research center. Not only does it seek to broaden youngsters' agency around public safety and drug policies, but it also devises and experiments with methodologies to enable their active participation.